Effect of Educational Video on Sanitation Knowledge Among Mothers of Stunted Toddlers in Bantul - Tresna Pangastuti Muslimah, Maestyca; Puji Ganefati, Sri; Haryono, Haryono; Haryanti, Sri (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Stunting is a nutritional problem in toddlers characterized by height-for-age below the growth standard. This condition remains a significant public health challenge in Indonesia, including in Bantul Regency, Special Region of Yogyakarta, where stunting prevalence is relatively high. One of the contributing factors to stunting is poor food and beverage sanitation, coupled with mothers’ limited knowledge of food hygiene. Health education is essential to improve mothers’ understanding and practices related to proper sanitation. This study aimed to analyze the effect of health education using educational videos on improving knowledge of food and beverage sanitation among mothers of stunted toddlers in Bibis Hamlet, Sewon, Bantul. This research employed a quasi-experimental design using a one-group pretest-posttest with a control group. The intervention group received education through an educational video, while the control group was provided with a leaflet. Primary data were collected through questionnaires administered before and after the intervention. The Mann–Whitney test was used for statistical analysis due to the non-normal distribution of the data. The results showed an increase in knowledge in both groups, with a higher increase observed in the intervention group (68%) compared to the control group (61%). Statistical analysis indicated a significant difference between the two educational methods. In conclusion, educational videos were found to be more effective in enhancing knowledge of food and beverage sanitation among mothers of stunted toddlers. This method can serve as a practical and accessible health education strategy to support sustainable stunting prevention efforts in the community.